Byzantinische Rechtsgeschichte in Frankfurt – eine Bilanz - Wolfram Brandes (Rechtsgeschichte - Legal History)
From 1974 to the end of 2020, the history of Byzantine law was researched in Frankfurt, initially funded by the German Research Foundation and then by the Göttingen Academy of Sciences. The article offers an overview of the most important research foci and, above all, of the results, tangible in a multitude of publications (editions, studies). An extensive bibliographical appendix documents the work of the research centre »Edition und Bearbeitung byzantinischer Rechtsquellen«.